Stigma Impact on Psychiatry Patient Management (International Journal of Food and Nutritional Sciences, 2022)
The stigma connected to mental disorders or individuals with mental illnesses extends not just to the general population, but also to specialists. Medical students, without a doubt, constitute a significant portion of the professional health workforce, and their attitudes toward psychiatric illnesses play an important role in determining their future choice of psychiatry as a possible career and in dealing with psychiatric complaints in their clinical practice once they enter their profession. As a result, they play a significant role in shaping the impact of stigma on the quality of life of the mentally ill.In this review we have collected various subjective opinions of different populations and their attitudes towards psychiatry as a branch as well as psychiatric patients and their course of treatment